CHRONOSTRATIGRAPHY, COMPOSITION, AND ORIGIN OF NI-RICH SPINEL FROM THE LATE EOCENE FUENTE CALDERA SECTION IN SPAIN: ONE IMPACT OR MORE? - Robin E.; Molina E. (My University, 2006)
Here we report on the stratigraphic distribution and chemical composition of Ni-rich spine, a specific mineral tracer of meteorite impacts, in the Fuente Caldera section in Spain. A major peak in spinel abundance is observed in a biostratigraphic interval defined by the last occurrence of the planktic foraminifera Porticulasphaera semiinvoluta and the first occurrence of the planktic foraminifera Turborotalia cunialensis. Two other peaks of lower abundances are observed higher up in the same biostratigraphic interval, but geochemical considerations suggest that they likely originate from redeposition by turbiditic currents. Biostratigraphic correlations with the global stratotype section and point for the Eocene/Oligocene boundary of Massignano in Italy give an age of 35.4 ± 0.2 Ma (1σ) for the major peak. This age is indistinguishable from the age of the impact horizon at Massignano (35.5 ± 0.2 Ma) and within the age uncertainties for the Popigai (35.7 ± 0.2 Ma) and Chesapeake Bay (35.5 ± 0.5 Ma) craters. The Fuente Caldera spinel, as the Massignano spinel, is assumed to be a relic mineral of microkrystites, which are believed to derive from a unique source related to the Popigai impact crater. The morphologies and Cr compositions of the Fuente Caldera and Massignano spinel crystals are markedly different, however: the Fuente Caldera spinel occurs mostly as octahedral and skeletal crystals with 85% of the grains belonging to the Cr-rich magnetite series and 15% to the Fe-rich chromite series, whereas the Massignano spinel occurs mostly as dendritic crystals with 90% of the grains belonging to the Cr-poor magnetite series. It is unlikely that these differences are the result of post-depositional alteration processes because the compositions of the crystals, as well as their morphologies, are in general very similar to those reported for primary spinel crystals, i.e., spinel crystals present in meteorite fusion crust or synthetized from meteoritic material. In addition, spinel crystals have quite homogeneous compositions except for a few grains (<10%) showing Cr zonations, but these are assigned to primary crystallization processes. One possible explanation that is consistent with a single impact event producing spatial variations in spinel compositions and morphologies is that microkrystites are locally generated by the ablation in the atmosphere of impact debris. An alternative explanation is that Fuente Caldera and Massignano microkrystites derive from two closely spaced impact events, which however requires another, so-far unknown source crater for microkrystites. © The Meteoritical Society, 2006.
Keywords: Oligocene; Eocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен